2021
DOI: 10.5152/j.aott.2021.20208
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic double crush pudendal nerve entrapment syndrome after fracture of the pelvis: A case report

Abstract: Pudendal syndrome is primarily characterized by stress urinary incontinence, dysuria, sexual arousal syndrome, painful erections, and anal incontinence. The syndrome occurs when the pudendal nerve or one of its branches is compressed, stretched, or injured. Double crush is the compression of a peripheral nerve at two or more separate areas with various signs and symptoms. We, herein, aimed to introduce the case of a 42-year-old male who underwent the distal release procedure due to the diagnosis of “double cru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…In some cases, PNE, SUI, and AI may coexist. Ayik et al [ 22 ] reported a case with bilateral PNE following a pelvis fracture 27 years before. Proximal transgluteal PNN relieved rectal pain and resolved AI.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In some cases, PNE, SUI, and AI may coexist. Ayik et al [ 22 ] reported a case with bilateral PNE following a pelvis fracture 27 years before. Proximal transgluteal PNN relieved rectal pain and resolved AI.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, 70 full-text papers underwent further screening for appropriateness, leading to the exclusion of 49 additional papers. Finally, 21 papers met the inclusion criteria and were included [ 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 ]. Fig.…”
Section: Evidence Synthesismentioning
confidence: 99%
See 3 more Smart Citations